2020
DOI: 10.1371/journal.pone.0234412
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of nutritional countermeasures in microgravity and its ground-based analogues to ameliorate musculoskeletal and cardiopulmonary deconditioning–A Systematic Review

Abstract: A systematic review was performed to evaluate the effectiveness of nutrition as a standalone countermeasure to ameliorate the physiological adaptations of the musculoskeletal and cardiopulmonary systems associated with prolonged exposure to microgravity. A search strategy was developed to find all astronaut or human space flight bed rest simulation studies that compared individual nutritional countermeasures with non-intervention control groups. This systematic review followed the guidelines of the Cochrane Ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…Bedrest differs from space flight in that in space, the gravity variable is removed, but in bedrest the 1 g variable is still present but the individual no longer works against it. However, there can be rapid muscle and bone loss, with the bone loss quite variable, similar to what has been observed in space (Kos et al, 2013 ), and cardiovascular deconditioning as well (Fortrat et al, 2001 ; Orter et al, 2020 ; Sandal et al, 2020 ; Solbiati et al, 2020 ), which again mimics the observations from space. In addition, chronic bedrest can lead to impairment of neuro-functions related to memory, and these can be reversed by exercise (Friedl-Werner et al, 2020 ).…”
Section: Bedrest “Deconditioning” On Earth Parallels That Of Space Flightsupporting
confidence: 70%
“…Bedrest differs from space flight in that in space, the gravity variable is removed, but in bedrest the 1 g variable is still present but the individual no longer works against it. However, there can be rapid muscle and bone loss, with the bone loss quite variable, similar to what has been observed in space (Kos et al, 2013 ), and cardiovascular deconditioning as well (Fortrat et al, 2001 ; Orter et al, 2020 ; Sandal et al, 2020 ; Solbiati et al, 2020 ), which again mimics the observations from space. In addition, chronic bedrest can lead to impairment of neuro-functions related to memory, and these can be reversed by exercise (Friedl-Werner et al, 2020 ).…”
Section: Bedrest “Deconditioning” On Earth Parallels That Of Space Flightsupporting
confidence: 70%
“…One review 13 used qualitative methods to present a thematic analysis of technical documents from grey literature sources required to answer the technical nature of the research question. Three reviews 25,31,32 included bed rest spaceflight simulation studies and reported bed rest quality scores. One review 24 used the quality of partial gravity simulations to list how well various ground simulations are likely to accurately model astronaut biomechanical, cardiovascular and metabolic changes.…”
Section: Resultsmentioning
confidence: 99%
“…Recapitulation of ground-based loading cycles of daily activities during 84 days of bed rest attenuated, but did not eliminate, the decline in several musculoskeletal and cardiovascular health parameters 23 . Nevertheless, findings from systematic reviews indicate that nutritional countermeasures could ameliorate musculoskeletal and cardiopulmonary deconditioning 24 , while findings from bed rest studies indicate that including plyometric exercise (hopping and whole body vibration) may be adjunct options to mitigate musculoskeletal loss on exploration missions where resources are limited 25 . Finally, lower body negative pressure (LBNP) coupled with exercise could offset the spaceflight-induced headward shift in vascular and cerebrospinal fluid and mitigate declines in cardiorespiratory fitness 26 .…”
Section: Discussionmentioning
confidence: 99%